PENGARUH STRUKTUR CORPORATE GOVERNANCE, AUDIT TENURE, DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP INTEGRITAS LAPORAN KEUANGAN - Ocktavia Nicolin; Arifin Sabeni (Diponegoro Journal of Accounting, 2013)
This research aims to analyze the effects of corporate governance structure, audit tenure and auditor industry specialization on integrity of financial statement of manufacturing sector in Indonesia’s companiesThe sample in this study were manufacturing sector companies listed in Indonesian Stock Exchange (IDX) in the periode 2008-2011. The number of sample used were 46 companies listed were taken by purposive sampling. The analysis method of this research used multiple linear regression analysis.The result of this research showed that independent commisioners and audit committee had positive and significat influence to integrity of financial statement; meanwhile ownership of managerial, ownership of institutional, audit tenure and auditor industry specialization had not significant effect to integrity of financial statement.